Employee Fit, Trust, Knowledge Sharing and Innovation Capabilities: Empirical Study on Indonesia Creative Industry - Nikolas Fajar Wuryaningrat; Paulus Kindangen; Greis Sendouw; Bode Lumanouw (Journal of International Conference Proceedings (JICP), 2018)
The sustainable competitive advantage of small and medium enterprises (SMEs) in creative industry could be demonstrated through the innovation capabilities. In knowledge management literature, knowledge sharing is the key effort to develop innovation capabilities. There are two contrasting theories of Knowledge sharing, Szulanski's (1996) theory assumes a knowledge sharing process is 'sticky' and ambiguous, while Nelson (1981) considered knowledge sharing to be an automatic process in an organization. This study arguing, employee fit will make impact on trust is a relatively new idea to bridging the two contrasting theories. Through the study, it was assuming that in order to develop the innovation capabilities of SMEs in the creative industry, knowledge sharing is needed, where trust is a crucial factor in knowledge sharing literature. However, building trust is not a simple matter, it assumed that the employee fit (person job fit and person organization fit) can be useful to build trust in the organization. The results of this study can be concluded that the SMEs in creative industry innovation capabilities directly influenced by employees fit. The employee fit also significant influenced on trust, and as expected trust strongly influenced knowledge sharing dimensions (knowledge donating and knowledge collecting. Surprisingly, knowledge sharing dimensions did not influence on innovation capabilities as expected before. The possibility reason, that knowledge sharing dimensions could not make any significant effect due of the concept of innovation funnel and absorptive capacity, which explained that, the more knowledge could achieved, the less knowledge could absorb. Keywords: knowledge sharing, innovation capabilities, person job fit, person organization fit, trust